Kindergarten Teacher's Views of Science Learning Practices in Schools - Harlistyarintica, Yora; Suyanto, Slamet (Universitas Negeri Malang, 2022)
This study aims to reveal the views of kindergarten teachers about science learning, the form of activities, the methods used, and the difficulties faced. This research uses descriptive qualitative research. The data were collected using semi-structured interviews with six kindergarten teachers who were selected by purposive sampling technique. Data were analyzed using the interactive model of Miles & Huberman. The results showed: 1) all teachers were of the view that science learning in childhood was very important to implement, 2) activities in science learning are carried out according to the learning theme, but two out of six teachers add activities spontaneously and follow natural phenomena, 3) the children's most preferred experimental method when doing science activities, and 4) difficulties faced by the teacher regarding tools and materials.